2017
DOI: 10.18293/seke2017-039
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Classification of Review Comments in Pull-based Development Model

Abstract: Abstract-The pull-based model, widely used in distributed software development, allows any contributor to fork a public repository, package contributions as a pull-request, and then merge back to the original repository. Code review is one of the most significant stages in pull-based development. It ensures that only high-quality pull-requests are accepted, based on the in-depth discussion among reviewers. Thus, automatically identifying what reviewers are talking about in the discussions is benificial to bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Determining the usefulness of code reviews. A study of three projects developed a taxonomy of review comments [163,164]. After training a classifier and categorizing 147K comments, they found that inexperienced contributors tend to produce code that passes tests while still containing issues, and external contributors break project conventions in their early contributions.…”
Section: Mcr Themes and Contributionsmentioning
confidence: 99%
“…Determining the usefulness of code reviews. A study of three projects developed a taxonomy of review comments [163,164]. After training a classifier and categorizing 147K comments, they found that inexperienced contributors tend to produce code that passes tests while still containing issues, and external contributors break project conventions in their early contributions.…”
Section: Mcr Themes and Contributionsmentioning
confidence: 99%
“…LDA is shown to have degraded performance for short text [24] due to reduced word co-occurrence in short texts for topic extraction. Code review comments are relatively short pieces of text [25]. Therefore, we considered topic modeling models suitable for short text, as suggested by Qiang et al [18].…”
Section: B Natural Language Processing Model Selectionmentioning
confidence: 99%